The Russian Discovery of Japan, 1670-1800 - Wells, David (Routledge, 2019)
The book includes key historical documents, some translated into English for the first time. The book is a prequel to the author's previous book, Russian Views of Japan, 1792-1913: An Anthology of Early Travel Writing (Routledge, 2004).